Hepatitis D infection in Brazil: Prevalence and geographical distribution of anti-Delta antibody - Lago, Barbara V.; Mello, Francisco C. A.; Barros, Tairine M.; Mello, Vinicius M.; Villar, Livia M.; Lewis-Ximenez, Lia L.; Pardini, Maria Inês M. C. [UNESP]; Lampe, Elisabeth (Wiley, 2018)
In Brazil, the Amazon Basin is endemic for hepatitis D virus (HDV) infection; however, studies in other regions of the country are scarce. This study aims to map the seroepidemiological situation of anti-Delta antibodies in chronic hepatitis B carriers in all five Brazilian geographic regions. Serum samples from 1240 HBsAg positive individuals (55.4% men; mean age 43.1 ± 13.4 years) from 24 of 26 Brazilian states were tested for the presence of anti-Delta antibodies using a commercial immunoassay. Anti-Delta antibodies were detected in 40 samples (3.2%; 52.5% female; mean age of 38.1 ± 13.8 years). Age less than 20 years was significantly associated with anti-HDV positivity (P < 0.001). The distribution of anti-Delta differed markedly in the diverse regions of the country. The highest prevalence of anti-HDV was found in the North (8.5%; P < 0.001), followed by Central West (2.5%), Southeast (1.7%), Northeast (0.8%), and South (0.0%). Anti-Delta antibodies were detected in 12 states, but more than 60% of the positive cases were observed in two states, Amazonas and Acre, located in the western portion of the Amazon region. The overall HDV prevalence of 3.2% emphasizes that HDV is far from being a disease under control in Brazil. Despite the low HDV prevalence in non-endemic regions, this infection persists as a major concern in two states (Acre and Amazonas) in the north of the country, indicating that a continuous epidemiological surveillance program should be implemented in all Brazilian regions.
Keywords: Brazil; HDV; seroepidemiology